Imaging-Genomics in Glioblastoma: Combining Molecular and Imaging Signatures - Liu, Dongming; Chen, Jiu; Hu, Xinhua; Yang, Kun; Liu, Yong; Hu, Guanjie; Ge, Honglin; Zhang, Wenbin; Liu, Hongyi (Frontiers in Oncology, 2021)
Based on artificial intelligence (AI), computer-assisted medical diagnosis can scientifically and efficiently deal with a large quantity of medical imaging data. AI technologies including deep learning have shown remarkable progress across medical image recognition and genome analysis. Imaging-genomics attempts to explore the associations between potential gene expression patterns and specific imaging phenotypes. These associations provide potential cellular pathophysiology information, allowing sampling of the lesion habitat with high spatial resolution. Glioblastoma (GBM) poses spatial and temporal heterogeneous characteristics, challenging to current precise diagnosis and treatments for the disease. Imaging-genomics provides a powerful tool for non-invasive global assessment of GBM and its response to treatment. Imaging-genomics also has the potential to advance our understanding of underlying cancer biology, gene alterations, and corresponding biological processes. This article reviews the recent progress in the utilization of the imaging-genomics analysis in GBM patients, focusing on its implications and prospects in individualized diagnosis and management.